Modelling seasonal HFMD with the recessive infection in Shandong, China - Yangjun Ma; Maoxing Liu; Qiang Hou; Jinqing Zhao (Mathematical Biosciences and Engineering)
Hand, foot and mouth disease (HFMD) is one of the majorpublic-health problems in China. Based on the HFMD data of the Department of Health of Shandong Province, we propose a dynamic model with periodic transmission rates to investigate the seasonal HFMD. After evaluating the basic reproduction number, we analyze the dynamical behaviors of the model and simulate the HFMD data of Shandong Province. By carrying out the sensitivity analysis of some key parameters, we conclude that the recessive subpopulation plays an important role in the spread of HFMD, and only quarantining the infected is not an effective measure in controlling the disease.